Too Many Crises or Just Another Leap Forward – An Essay - Nuta, Florian (EuroEconomica, 2023)
Historically, the world's major crises were turning points in human history, and human evolution went through many such moments. At times, these momentous events were a vital menace for humans, endangering vast populations and regions. Even if it was about exiting the last Ice Age, a massive plague, or huge migrations, the humans were tested for their best resilience capacity and endurance skills. Learning from past experiences as a race, not only at the individual level, was the leading quality that separated humans from other species. Our civilization overcame those critical moments, advancing society to the subsequent level of development.